EXPLORING THE CONSISTENCY BETWEEN TEACHERS' AND PARENTS' RATINGS OF CHILDREN'S LANGUAGE SKILLS - Trinite, Baiba; Tomele, Gundega; Rascevska, Malgozata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Aim: The study investigated the correspondence between parent and teacher assessments of 3 to 6-year-old children's language skills using the Expressive and Receptive Language Scales from the Early Childhood Developmental Screening Toolkit – BAASIK (an acronym in Latvian). Material and methods: Ninety-five preschool teachers and 424 parents participated in an online survey assessing the expressive and receptive language skills of children aged 3 to 6 years. Results: Spearman's correlation analysis revealed statistically significant (p < .001) moderate to strong correlations between the ratings of children’s language skills by parents and teachers. For the Receptive Language Scales, correlations ranged from rS = .43 to rS = .6, and for the Expressive Language Scales, from rS = .54 to rS = .64. Conclusions: The study confirmed that parents’ and teachers’ assessments of children’s expressive and receptive language skills are significantly correlated. The BAASIK Expressive and Receptive Language Scales used by both parents and teachers could be effective for early screening, potentially aiding in the prompt identification of language development issues and the subsequent referral to speech and language therapy services.